Le prix des offices en Nouvelle Espagne : l’exemple de Puebla (1560-1639) - Émilie Senmartin (Les Cahiers de Framespa)
In New Spain, municipal offices used to be obtained by royal favour before the end of the sixteenth century. They were thereafter sold to the highest bidder, a phenomenon which provoked tensions as buying offices was synonymous with acquiring honorability and power in the city. These strong tensions can be explained by the lack of clarity concerning the price of the office. Moreover, the composition of the Cabildo was durably modified by the introduction of the principle of venality which prevented a section of the poblana population from gaining access to the Cabildo. However, venality was also an opportunity for a new category of rich traders to become members of the until then strongly closed Cabildo.